Effect of Earning Management on Incentive Compensation Moderated by Women Executive Director on Board - Serly Serly; Melani Melani (Enrichment : Journal of Management, 2022)
This study aims to determine the Effect of Earning Management on Incentive Compensation Moderated by Female Executive Director On Board in Manufacturing Companies Listed on the Indonesia Stock Exchange. The design in this study is quantitative in nature with an emphasis on how to study theory and things in measuring variables with numbers and how these data can follow statistical data or procedures. As well as in terms of the purpose of this study can be characterized as a theoretical characteristic in presenting the basics as well as whether there is an influence or linkage to a significant influence or not in the connected variables. In this study, annual data is collected from the financial reports of manufacturing companies listed on the IDX via the www.idx.co.id page from 2016 to 2021. The results of this study show that there is no effect of Earning Management on Incentive Compensation Moderated by the Female Executive Director on Board, there is no influence between Earning Management on Incentive Compensation. The Adjusted R Square test results obtained an Adjusted R Square value of 0.724708 so that it can be stated that the independent variables simultaneously have a significant effect on the dependent variable by 72.47%, the rest is influenced by other variables not used in this study.